PTH Signaling in Osteoprogenitors Is Essential for B‐Lymphocyte Differentiation and Mobilization. (20th July 2015) - Panaroni, Cristina; Fulzele, Keertik; Saini, Vaibhav; Chubb, Rhiannon; Pajevic, Paola Divieti; Wu, Joy Y
ABSTRACT: Cells of the osteoblast lineage provide critical support for B lymphopoiesis in the bone marrow (BM). Parathyroid hormone (PTH) signaling in osteoblastic cells through its receptor (PPR) is an important regulator of hematopoietic stem cells; however, its role in regulation of B lymphopoiesis is not clear. Here we demonstrate that deletion of PPR in osteoprogenitors results in a significant loss of trabecular and cortical bone. PPR signaling in osteoprogenitors, but not in mature osteoblasts or osteocytes, is critical for B‐cell precursor differentiation via IL‐7 production. Interestingly, despite a severe reduction in B‐cell progenitors in BM, mature B‐lymphocytes were increased 3.5‐fold in the BM of mice lacking PPR in osteoprogenitors. This retention of mature IgD + B cells in the BM was associated with increased expression of vascular cell adhesion molecule 1 (VCAM1) by PPR‐deficient osteoprogenitors, and treatment with VCAM1 neutralizing antibody increased mobilization of B lymphocytes from mutant BM. Our results demonstrate that PPR signaling in early osteoblasts is necessary for B‐cell differentiation via IL‐7 secretion and for B‐lymphocyte mobilization via VCAM1. © 2015 American Society for Bone and Mineral Research.